Novel factor in olfactory ensheathing cell‐astrocyte crosstalk: Anti‐inflammatory protein α‐crystallin B. Issue 4 (12th December 2020) - Saglam, Aybike; Calof, Anne L.; Wray, Susan
Abstract: Astrocytes are key players in CNS neuroinflammation and neuroregeneration that may help or hinder recovery, depending on the context of the injury. Although pro‐inflammatory factors that promote astrocyte‐mediated neurotoxicity have been shown to be secreted by reactive microglia, anti‐inflammatory factors that suppress astrocyte activation are not well‐characterized. Olfactory ensheathing cells (OECs), glial cells that wrap axons of olfactory sensory neurons, have been shown to moderate astrocyte reactivity, creating an environment conducive to regeneration. Similarly, astrocytes cultured in medium conditioned by cultured OECs (OEC‐CM) show reduced nuclear translocation of nuclear factor kappa‐B (NFκB), a pro‐inflammatory protein that induces neurotoxic reactivity in astrocytes. In this study, we screened primary and immortalized OEC lines to identify these factors and discovered that Alpha B‐crystallin (CryAB), an anti‐inflammatory protein, is secreted by OECs via exosomes, coordinating an intercellular immune response. Our results showed that: (a) OEC exosomes block nuclear NFκB translocation in astrocytes while exosomes from CryAB‐null OECs could not; (b) OEC exosomes could be taken up by astrocytes, and (c) CryAB treatment suppressed neurotoxicity‐associated astrocyte transcripts. Our results indicate CryAB, as well as other factors secreted by OECs, are potential agents that can ameliorate, or even reverse, the growth‐inhibitory environment created by neurotoxic reactive astrocytes following CNS injuries. Main Points: Astrocytes uptake OEC‐secreted exosomes. WT OEC‐exosomes, but not CryAB‐null OEC‐exosomes, block nuclear NFκB translocation in astrocytes. CryAB, and other factors secreted by OECs, suppresses multiple neurotoxicity‐associated astrocyte transcripts.